Le courtage de l’assurance de dommages : une vision d’avenir - Commission de recherche – orientation – planification (CROP), La (Assurances)

(untitled) (HEC Montréal, 1994)
The article examines the Property & Casualty insurance industry and the evolution of insurance brokerage in the wake of the removal of barriers between the four financial pillars. It also looks at the challenges that lie ahead for the insurance industry following the foray of stronger and better equipped players into this market.